Lá no caminho eu deixei meu sentinela: territorialidade e movimento de um terreiro de Umbanda - Lânia Mara Silva (2018)
Through this work one navigates in order to understand how the people of the terreiro conceive of notions like place, neighborhood and traditional territory. From the umbanda terreiro Casa de Caridade Pai Jacob do Oriente (CCPJO), from conversations with the caretaker of this house, Ricardo de Moura and from his own experiences, one can perceive that the conception of place is much broader, involving multiple relations which overlap without being excluded. From the Lagoinha neighborhood, where CCPJO is located, a path was traced in which neighborhood, physical space of the terreiro, history, syncretism, ancestrality merge to demonstrate how the Afro-Brazilian cosmology is distinct in its conceptions. Finally, the navigation goes towards the winds, which led us to weave the map of the territory of traditional use of the Casa de Caridade Pai Jacob do Oriente, which allowed a greater understanding of the notions of place of use and belonging of this people of terreiro.